Acceptance or decline of requests to review manuscripts: A gender-based approach from a public health journal. (17th February 2018) - Felícitas Domínguez-Berjón, María; Godoy, Pere; Ruano-Ravina, Alberto; Negrín, Miguel Ángel; Vives-Cases, Carmen; Álvarez-Dardet, Carlos; Bermúdez-Tamayo, Clara; López, María José; Pérez, Glòria; Borrell, Carme
ABSTRACT: Peer review in the scientific publication is widely used as a method to identify valuable knowledge. Editors have the task of selecting appropriate reviewers. We assessed the reasons given by potential reviewers for declining a request to review, and the factors associated with acceptance, taking into account the difference in the sex of the reviewer. This is a descriptive study of the review requests from a public health journal ( Gaceta Sanitaria ) with an enforced gender policy. The dependent variables were requests, response to requests, reasons potential reviewers gave for declining requests and time to review. We carried out a descriptive analysis of these indicators and applied logistic regression to analyze factors (professional and research/review experience) associated with having done at least one review in 2014–2015. Results were stratified by sex. Journal editors sent 1, 775 requests to 773 potential reviewers; 52.3% of whom reviewed at least one manuscript. Of the 396 declined requests (22.3%), the most common reasons were lack of time and of experience (88.1%). No differences were observed by sex. In the multivariate analysis, having reviewed for the journal in previous years showed the strongest association with acceptance. Specific analyses of data on requests reviewers may be useful for improving the acceptance rates to review. This study did not show gender differences in several indicators of the reviewing process.